Listening still [large type] - Griffin, Anne, 1969- (Center Point Large Print, 2022)
"Jeanie Masterson has a gift: she can hear the recently dead and give voice to their final wishes and revelations. Inherited from her father, this gift has enabled the family undertakers to flourish in their small Irish town. Yet she has always been uneasy about censoring some of the dead's last messages to the living. Unsure, too, about the choice she made when she left school seventeen years ago: to stay, or leave for a new life in London with her charismatic teenage sweetheart. So when Jeanie's parents unexpectedly announce their plan to retire, she is jolted out of her limbo."--